Challenging global accountability: The intersection of contracts and culture in the World Bank - Nilima Gulrajani (University of Oxford, Global Economic Governance Programme (GEG), 2010)
Global accountability is commonly understood as a contractual mechanism between principals and agents where standards of behavior are objective and respond to functional needs, agents are autonomous, motivations are self-interested and practices are procedural. This paper theorizes an alternative to this rationalist framing of global accountability anchored in theories of sociological institutionalism that rest on a constructivist ontology. In this latter perspective, standards of accountable global behaviour derive from socially constructed global cultural norms governed by the logic of appropriateness that both produces and contours embedded global actions. The argument is made that epistemologically distinguishing and empirically uniting contractual and cultural understandings offers new vistas for understanding the challenge of global accountability. This is illustrated with a comparative investigation of contractual accountability mechanisms and cultural accountability norms inside two World Bank country offices in Bolivia and Vietnam.
Keywords: 330; Vertragstheorie; Prinzipal-Agent-Theorie